Assessment of Critical Barriers to Industry 4.0 Adoption in Manufacturing Industries of Bangladesh: An ISM-Based Study - Hossain, Sourav; Hassan, Sanjida; Karim, Rubayet (Brazilian Journal of Operations & Production Management, 2023)
Purpose: Regardless of the potential benefits of Industry 4.0, firms are still experiencing difficulties in properly integrating new technologies into their business. This study focuses on addressing critical barriers to implementing Industry 4.0 in the manufacturing industries of Bangladesh with a view to exploring readiness. The paradigm of adopting new technologies is yet to be unlocked in Bangladesh, which serves as this study's motivating force. Approach: In order to accomplish the research objectives, "Interpretive Structural Modelling (ISM)" analysis is used, which identified and outlined the most significant barriers to adopting Industry 4.0. This was also combined with MICMAC analysis, which categorized the barriers based on their driving and dependent power. To evaluate the industries' preparedness, "cross-tabulation and frequency analysis" is performed using SPSS. Key findings: According to the findings, “Lack of technical knowledge about industry 4.0” has been identified as the most crucial barrier. Limitations of the study: To address the firm’s preparedness, we looked at responses from management personnel. Nevertheless, if we could do this on a larger scale, a better scenario of Bangladesh's manufacturing industries toward Industry 4.0 might be shown. Practical implication: The study's findings will be conceptually linked to relevant aspects of I4.0, particularly for strategic planning, decision-making, future opportunities, and formulating policy-related guidelines. Originality: While several studies concentrate on particular sectors adopting Industry 4.0, no study has been conducted on manufacturing industries focusing on the industry's preparedness, which makes this study distinctive.